(untitled) (Al-Farooq Journal of Sciences, 2026)
The use of biofillings as a new high-level solution in restorative dentistry has recently become possible due to their increased biocompatibility, durability, and aesthetic performance. The purpose of the study is to assess the clinical efficacy of Ceramic-based, Glass ionomer and Composite resin biofilling materials and, specifically, the satisfaction of patients, comfort following the treatment, and durability of materials after 6 months of the treatment. A cross-sectional retrospective study was done on a sample of 230 patients who had biofilling restorations in five dental clinics in Libya. A structured questionnaire was used to measure post-treatment sensitivity, aesthetic outcomes, durability, and general satisfaction to collect data. The performance of various biofilling materials was compared using statistical analysis. The findings indicated that 72 % (n=165) of the patients did not report any pain after the treatment, with only one in every ten patients 10% (n=23) reporting moderate sensitivity that necessitated follow-up. Aesthetically, 87% (n=200) of the respondents were satisfied with the natural look of their restorations. In terms of durability, 90% of biofilling was found to be intact after six months, but small chipping was noted in 3% of instances, mostly in high-stress areas. Ceramic-based biofillings of the considered materials received the highest performance score (4.8/5) due to the increased biocompatibility and mechanical strength. To sum up, biofillings are a consistent and efficient choice of restorations, with high patient satisfaction and clinical outcomes. Nevertheless, more material optimization is suggested to resolve minor problems with discoloration and wear. The use of zinc oxide nanotechnological innovations and bioactive surface treatment could offer a potential solution in antimicrobial effect, stain resistance, and durability.